What do project management practitioners think governance is? A study on perceptions in Queensland, Australia. Issue 5 (7th May 2020) - McGrath, Stephen Keith; Whitty, Stephen Jonathan
Abstract : Purpose: To determine if there is confusion in governance terminology amongst experienced management and project management practitioners. Design/methodology/approach: Practitioner interviews and subsequent analysis. Findings: Significant differences in governance terminology were found. The participants had nevertheless arrived at similar operating arrangements for their committees, even though they came from different segments of different industries and did not agree on the definition of governance. It was possible to develop a list of working parameters for operation of these committees from their responses. The labelling of committees associated with governance as steering or decision-making was found to be problematic and various causes/motivations for the differing definitions of governance having arisen were detected. These ranged from altruism, through dogmatic belief in particular frameworks, to enhancing career prospects/ego. Research limitations/implications: The sample came from organisations and industries in one state in one country. The need for review of governance terminology used in various project management practitioner reference documents and methodologies was identified. Practical implications: Projects and business alike can potentially achieve improvements in efficiency and effectiveness through consistency of terminology and the clarity this brings to governance arrangements and committee operations. Social implications: Creation of a unifying feature within the project and management literature, shifting the understanding of governance and its boundaries and limitations. This will help progress governance from complexity to simplicity, from an art to an understandable practice, from a concept that has been hijacked for partisan and political gain to a lean social tool which can be put to use for the benefit of organisations, whether public, charitable or private. Originality/value: The value is clarity – resulting in the avoidance of confusion and misunderstanding together with their consequent waste of time, resources and money.